The 3D reconstructed skin micronucleus assay: considerations for optimal protocol design. (3rd December 2019) - Kidd, Darren; Phillips, Sarah; Chirom, Teresa; Mason, Nicky; Smith, Robert; Saul, Jim; Whitwell, James; Clements, Julie
Abstract: Implementation of the seventh amendment to the EU Cosmetics Directive has driven much research into suitable in vitro alternative assays to support satisfactory risk assessments. One such assay is the reconstructed skin micronucleus (RSMN) assay. First reported in 2006, further development occurred and a standard protocol was published in 2011. To evaluate and optimise the assay at Covance Laboratories, we tested nine chemicals [4-nitrophenol (4-NP), cyclohexanone (CH), 2-ethyl-1, 3-hexanediol (2-EHD), methyl methansulfonate (MMS), mitomycin C (MMC), ethyl nitrosourea (ENU), benzo[a]pyrene (BaP), cyclophosphamide (CPA) and vinblastine (VIN)] using the EpiDerm™ 3D skin model (MatTek Corporation ®, IVLSL, Bratislava, Slovakia) and compared the data using the standard 48-h treatment regimen and also an emerging 72-h treatment protocol. The EpiDerm™ tissue has reportedly some metabolic capacity but data using 48-h treatments has provided mixed results. Our investigations demonstrate that the two chemicals requiring metabolic activation (BaP and CPA) were negative following the 48-h protocol but were clearly positive following 72-h treatment. Furthermore, Replication Index (RI) data showed higher RI values in vehicle control treatments (indicating increased cell division) across the treatment set following 72-h treatments. A general greater magnitude of micronucleus (MN) induction was also observed following test chemical treatment. These data suggest that the 72-h treatment protocol is more suitable as a standard approach for the detection of clastogenic, aneugenic and metabolically activated chemicals in the RSMN assay. For further assay optimisation, we compare the statistical power of scoring cells from duplicate or triplicate cultures per treatment concentration and provide recommendations.